Developing Courses of Spanish for Specific Purposes in Agriculture to Bridge the Communication Gap Between the Hispanic Workforce and English-Speaking Veterinary and Animal Sciences Students - Leonor Salazar; Allen Jimena Martinez Aguiriano; Silvana Pietrosemoli; Arlene Garcia (Animals)
This study addresses the integration of Spanish for Specific Purposes in Agriculture (SSPA) into the curricula of English-speaking veterinary and animal sciences students at three collaborating universities (Texas Tech University School of Veterinary Medicine, North Carolina State University, and Tarleton State University), to bridge communication gaps in agricultural settings. We designed and implemented three SSPA courses focused on key areas such as animal health, welfare, and food safety, using insights from industry professionals. The courses incorporated contextualized language instruction, including vocabulary, grammar, and practical communication scenarios relevant to the field. Teaching materials including interactive resources and metacognitive strategies were developed to enhance learning and engagement. The results showed that while the courses improved students’ communication skills, challenges such as technical issues and balancing academic commitments required adjustments to course delivery. Significant differences in performance were observed between institutions, with a considerable impact on the course completion rates and final test scores. The study concludes that SSPA courses significantly enhance the ability of veterinary and animal sciences students to effectively communicate with the Hispanic workforce, providing a model for similar language integration efforts in specialized fields.